Let John's age now be J and his son's current age be S.

The looking at the ages now, J + 13 = 3S : Thus S = (J + 13) ÷ 3

And looking at 6 years ago, (J - 6) - 14 = 2(S - 6) : J - 20 = 2S - 12 : 2S = J - 8 : S = (J - 8) ÷ 2

Putting the two equations for S equal to one another gives :-

(J + 13) ÷ 3 = (J - 8) ÷ 2 : 2(J + 13) = 3(J - 8) : 2J + 26 = 3J - 24 : J = 50

John is 50 years old.

The looking at the ages now, J + 13 = 3S : Thus S = (J + 13) ÷ 3

And looking at 6 years ago, (J - 6) - 14 = 2(S - 6) : J - 20 = 2S - 12 : 2S = J - 8 : S = (J - 8) ÷ 2

Putting the two equations for S equal to one another gives :-

(J + 13) ÷ 3 = (J - 8) ÷ 2 : 2(J + 13) = 3(J - 8) : 2J + 26 = 3J - 24 : J = 50

John is 50 years old.